KESULITAN BELAJAR MAHASISWA DALAM MATA KULIAH DRAPING 1 PADA PROGRAM STUDI D3 TATA BUSANA JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - febrianita, maria; zahri, wildati; yasnidawati, yasnidawati (Journal of Home Economics and Tourism, 2013)
The background of the problem in this research is thedifficulties experienced  by student’s learning the Family WelfareDepartment of the Faculty of Engineering University of  Padangcourses draping1 marked  by as student who get low scores. Thepurposes of this study was to determine how high the difficulties  theFamily Welfare Department of the Faculty of EngineeringUniversity of  Padang  student learning in a subject draping 1 interms of understanding the material and learning facilities. Thisresearch is descriptive kuantitatif. The population in this study werestudents majoring the Family Welfare Department fashion  coursesD3 BP 2010/2011 the number of 33 people. The sample in this studyis determined by the total sampling technique, the entire populationwere sampled. The data use in this research is the primary data.Research instrument is based on indicator, data collection obtainedfrom  respondents through question  naires charging. The analysisshowed that students learning difficulties seen from understandingthe material included in the high category with 68.2%. thepercentage of students learning difficulties including high categorywith the percentage of 63%. Difficulty learning students in subjectscategorized draping 1 high percentage of 67%. This means thatstudents still find difficulties in the courses draping 1. Expectedresults of this research to faculty and student. Kata kunci: Kesulitan Belajar Mahasiswa, Draping 1